The Influence of E-Wom on the Users’ Purchase Decision of M-Learning Apps - Asadi Damavandi, Azade; Bangero, Hyacinth; Asadi Damavandi, Ghazale (Jurnal Minds: Manajemen Ide dan Inspirasi, 2025)
This study examines the influence of electronic word-of-mouth (e-WOM) on information adoption and purchase intentions in mobile learning (M-learning) applications. By extending the Information Adoption Model (IAM) to an educational technology context, it contributes theoretically to understanding how digital peer communication shapes technology uptake. A survey of 345 Iranian young adults reveals that e-WOM significantly affects adoption decisions, with perceived usefulness emerging as a central driver of purchase intentions. The findings underscore the dual role of positive and negative user reviews in shaping app reputation and credibility. Beyond its contextual focus on Iran, where app usage is restricted, the study advances research on e-WOM dynamics in digital learning ecosystems of developing countries. The results provide practical insights for marketers, developers, and educational institutions seeking to leverage user-generated content to enhance trust, strengthen credibility, and foster wider acceptance of M-learning solutions.